2013
DOI: 10.1089/aid.2012.0284
|View full text |Cite
|
Sign up to set email alerts
|

Profile of HIV Type 1 Coreceptor Tropism Among Kenyan Patients from 2009 to 2010

Abstract: A switch of HIV coreceptor usage from CCR5 to CXCR4 occurs in AIDS pathogenesis and may play a critical role in the use of entry inhibitors. To determine the potential usefulness of maraviroc and other CCR5 antagonists among drug-naive and experienced patients in Kenya, the env-C2-V3 gene was successfully sequenced in samples from 176 (98 men and 78 female) consenting subjects between January 2009 and December 2012. In silico CPSSM, webPSSM/, and (ds) Kernel tools were used in predicting coreceptor usage. On t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Subtype C for example has been shown to preferentially use CCR5 and to rarely induce syncytia [43, 44]. A few studies involving Kenyan subjects have shown majority of circulating HIV to be R5 tropic, and mostly due to the predominance of R5-tropic HIV subtype A [27, 28, 45]. Significant variations became apparent when tropism is disaggregated by viral subtype, with majority of subtype A1, C and A1 recombinants being R5 tropic.…”
Section: Discussionmentioning
confidence: 99%
“…Subtype C for example has been shown to preferentially use CCR5 and to rarely induce syncytia [43, 44]. A few studies involving Kenyan subjects have shown majority of circulating HIV to be R5 tropic, and mostly due to the predominance of R5-tropic HIV subtype A [27, 28, 45]. Significant variations became apparent when tropism is disaggregated by viral subtype, with majority of subtype A1, C and A1 recombinants being R5 tropic.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is also some correlation with HIV-1 genetic variants. R5 viruses are more often detected in subtype A, regardless of the stage of the disease [20], [21], [22].…”
Section: Introductionmentioning
confidence: 99%
“…8 A strong selection for viral variants using CCR5 as a coreceptor occurs during transmission, as most children are infected with R5 viruses. [9][10][11][12] Prevention of mother-to-child transmission (PMTCT) of HIV-1 is one of the key components of the worldwide response to the pandemic and is based on the prophylactic use of antiretroviral drugs (ARVs). In developed countries, MTCT of HIV-1 has been reduced to less than 2% by combination antiretroviral therapy (ART), selective caesarian delivery, and avoidance of breastfeeding.…”
Section: Introductionmentioning
confidence: 99%